Citizenship education to face the challenges of the millennial generation and generation Z - Dadang Mulyana (Sean Institute, 2024)
In this digital and globalization era, the millennial and Gen Z generations are faced with complex social, political and economic issues that require a deep understanding of active and sustainable citizenship. This research aims to explore the effectiveness of citizenship education in preparing the millennial generation and generation Z to face contemporary challenges. This research uses a qualitative approach with descriptive methods. The results of the research show that the implementation of Citizenship Education is effective in shaping the character of the millennial generation and generation Z. The respondents showed a deep understanding of the government structure, rights and obligations of citizens, and showed positive attitudes such as responsibility towards society, tolerance for differences and active participation. in social or political activities. Citizenship skills, such as argumentation, dialogue, and collaboration, are also visible in their contributions to solving social problems and participating in community development projects. Thus, the research results confirm that Citizenship Education has a positive impact in equipping the younger generation with the knowledge and skills needed to play an active role in society, in accordance with the objectives of citizenship education.